A Production systems study of Saniwares - Alaan, Ailene B. (College of Engineering, 1995)
In documenting all existing department operations and other areas of importance for Saniwares as required, the total quality management control system and other manpower concerns have been given special attention to by the proponents of this study. And in determining the best feasible solution to these areas, a supporting data and other tables where gathered. For the Total Quality Control (TQC) area, the data for the number of defects were gathered for one month via production worksheets which states the allowable loss per operation and was analytically compared to the actual observed defects for that particular month. These are then plotted through some statistical quality control procedures to determine whether or not it does fall within the lower and upper limits set by company standards. It was thus determined that although the data may fall within the specified limits, significant losses are still observed in the same production worksheet. And the minimization defects were of major concern, further investigation as performed with the aid of a cause and effect diagram which revealed two viable causes for such deficiencies, namely: the poor training given by their workers (mostly casuals) and the insufficient inspection procedures implemented per operation as evidenced through the documentation of existing department operations. Thus, a proposed flow of inspection procedures for checking the Total Quality Control has been proposed as it is found to be a more simplified version for maintaining quality in the production process of the plant. Regarding the high degree of absenteeism due to the elimination of a former incentive program. The hiring of casual workers had induced a lower quality and quantity of output. A reinstatement of a long-time implemented incentive program is deemed to be necessary in order to elevate the motivational drive of the workers and to promote a higher morale in finding pride in their work. In effect, the deduction of the cost of defective wares must be imposed upon the worker responsible for such damage. This has proven tho be a proper consort of such a beneficial incentive program the group has proposed to be re-instated. The over-all implementation of all recommended actions can not only minimize the negative variance in the production output but also increase and improve the products produced by the workers while uplifting their drive and morale at the simultaneously.